Molecular and Cellular Roles of PI31 (PSMF1) Protein in Regulation of Proteasome Function - Li, Xiaohua (American Society for Biochemistry and Molecular Biology, 2014)
We investigated molecular features and cellular roles of PI31 (PSMF1) on regulation of proteasome function. PI31 has a C-terminal HbYX (where Hb is a hydrophobic amino acid, Y is tyrosine, and X is any amino acid) motif characteristic of several proteasome activators. Peptides corresponding to the PI31 C terminus also bind to and activate the 20 S proteasome in an HbYX-dependent manner, but intact PI31protein inhibits in vitro 20 S activity. Binding to and inhibition of the proteasome by PI31 are conferred by the HbYX-containing proline-rich C-terminal domain but do not require HbYX residues. Thus, multiple regions of PI31 bind independently to the proteasome and collectively determine effects on activity. PI31 blocks the ATP-dependent in vitro assembly of 26 S proteasome from 20 S proteasome and PA700 subcomplexes but has no effect on in vitro activity of the intact 26 S proteasome. To determine the physiologic significance of these in vitro effects, we assessed multiple aspects of cellular proteasome content and function after altering PI31 levels. We detected no change in overall cellular proteasome content or function when PI31 levels were either increased by moderate ectopic overexpression or decreased by RNA interference (RNAi). We also failed to identify a role of PI31 ADP-ribosylation as a mechanism for regulation of overall 26 S proteasome content and function, as recently proposed. Thus, despite its in vitro effects on various proteasome activities and its structural relationship to established proteasome regulators, cellular roles and mechanisms of PI31 in regulation of proteasome function remain unclear and require future definition.